Calcificaciones heterotópicas en paciente politraumatizado - María Soledad Trasante Borches; Marcela B. Giovenco; Nicolás E. Bernard; María Diehl; Gerardo Zanotti; Paula Russo; Diego Andresik (Revista del Hospital Italiano de Buenos Aires)
-